The Development, Verification and Evaluation of Container Closure Integrity Assessment of Prefilled Syringes Using Fluorescence Spectroflurometer - Shripad Deshpande; Deepak D. Kayande; Mazahar Farooqui; Parag Deshmukh (To Chemistry Journal, 2020)
The preference of Prefilled syringes is increased over all the vials as container closure systems for liquid injections, when facilitated or self-administration is required.However, prefilled syringes are more complex compared to container closure system(CCS) consisting of vial, rubber stopper and flip off. Container closure integrity assurance and verification has been a specific challenge for prefilled syringes as they feature several sealing areas. A comprehensive understanding of the container closure system is necessary for an appropriate container closure integrity assessment as well as for packagingdevelopment and qualification.